Phosphorylation of the neurogenic transcription factor SOX11 on serine 133 modulates neuronal morphogenesis. Issue 1 (December 2018) - Balta, Elli-Anna; Schäffner, Iris; Wittmann, Marie-Theres; Sock, Elisabeth; Zweydorf, Felix; Wittgenstein, Julia; Steib, Kathrin; Heim, Birgit; Kremmer, Elisabeth; Häberle, Benjamin; Ueffing, Marius; Lie, Dieter; et al.
Abstract The intellectual disability gene, Sox11, encodes for a critical neurodevelopmental transcription factor with functions in precursor survival, neuronal fate determination, migration and morphogenesis. The mechanisms regulating SOX11's activity remain largely unknown. Mass spectrometric analysis uncovered that SOX11 can be post-translationally modified by phosphorylation. Here, we report that phosphorylatable serines surrounding the high-mobility group box modulate SOX11's transcriptional activity. Through Mass Spectrometry (MS), co-immunoprecipitation assays andin vitro phosphorylation assays followed by MS we verified that protein kinase A (PKA) interacts with SOX11 and phosphorylates it on S133.In vivo replacement of SoxC factors in developing adult-generated hippocampal neurons with SOX11 S133 phospho-mutants indicated that phosphorylation on S133 modulates dendrite development of adult-born dentate granule neurons, while reporter assays suggested that S133 phosphorylation fine-tunes the activation of select target genes. These data provide novel insight into the control of the critical neurodevelopmental regulator SOX11 and imply SOX11 as a mediator of PKA-regulated neuronal development.